Factors Influencing the Retirement Planning Among Private Sector Workers in Malaysia - Othman, Mohd Noor Azman bin; Rashid, Mas Anom binti Abdul; Maura, Zulhida binti Abd; Seman, Shahri Abu (Journal of Ecohumanism, 2024)
The rising cost of living and the increase life expectancy in Malaysians calls for a study in the preparedness of the Malaysian soon-to-be retirees as Malaysian will be a super aged nation by 2056. There is concerned on whether the current employees has enough savings for their retirements because statistics has shown that many retirees and elderlies facing dilemma of not having sufficient money to maintain and cover a comfortable retirement and medical expenses. Over time, this problem is becoming worst. Lack of financial comprehension, inadequacy of private sector workers’ EPF savings and lack of goal clarity would lead to fallacious retirement planning decisions among private sector workers. This study aims to examine the influence of financial literacy, personal attitudes, saving behaviour and goal clarity on retirement planning among workers in Malaysian private sector. This is a quantitative study and survey was used to collect data from 107 private sector workers in Kuala Lumpur. The results shows that financial literacy, personal attitude, saving behaviour and goal clarity do have significant relationship towards retirement planning among workers, however, further analysis carried out singled out goal clarity as the main predictor towards retirement planning. This finding can be beneficial to relevant agencies and bodies to address these factors to encourage an effective retirement planning among their employees so that they can enjoy their retirement years.